A multi-state approach to modelling intermediate events and multiple mortgage loan outcomes - Richard Chamboko; Jorge Miguel Ventura Bravo (Risks, 2020)
This paper proposes a novel system-wide multi-state framework to model state occupations and the transitions among current, delinquency, default, prepayment, repurchase, short sale and foreclosure on mortgage loans. The approach allows for the modelling of the progression of borrowers from one state to another to fully understand the risks of a cohort of borrowers over time. We use a multi-state Markov model to model the transitions to and from various states. The key factors affecting the transition into various loan outcomes are the ability to pay as measured by debt-to-income ratio, equity as marked by loan-to-value ratio, interest rates and the property type. Our findings have broader policy implications for better decision-making on granting loans and the design of debt relief and mortgage modification policies.
Keywords: C01; C41; C53; C58; E51; G21; 330; credit risk; survival analysis; multi-state models; delinquency; recovery; relief programs; mortgage modification